Peran Dukungan Motivasi Diri dalam Meningkatkan Keberhasilan Pemulihan Pecandu Narkoba: Studi di IPWL Bukit Doa - Panggabean, Vannya Tesalonika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the role of self-motivation support in improving the recovery success of drug addicts at IPWL Bukit Doa. Using a qualitative descriptive approach, the research found that rehabilitation programs integrating spiritual, psychosocial, and character-building aspects are effective in fostering participants’ intrinsic motivation. Initially external motivation gradually develops into strong intrinsic motivation through internalization and positive social interactions. A supportive social environment and intensive mentoring further strengthen the recovery process. The findings indicate that sustained drug-free living after rehabilitation is highly influenced by the strength of self-motivation formed during the program. Therefore, synergy between institutions, families, and communities is essential to support sustainable recovery.